Interspecific Comparisons with Chloroplast SSR Loci Reveal Limited Genetic Variation in Nigerian Montane Forests: A Study on Cordia Millenii (West African Cordia), Entandrophragma Angolense (Tiama Mahogany), and Lovoa Trichilioides (African Walnut). (March 2016) - Thia, Joshua A.; Hale, Marie L.; Chapman, Hazel M.
The montane forests of south-eastern Nigeria are of immense conservation value due to their high levels of biodiversity and endemism. Yet despite increasing anthropogenic disturbance and forest fragmentation, little is known about the genetics of resident tree populations. We used a set of conserved chloroplast simple sequence repeat (SSR) primers to quantify and directly compare genetic diversity in three tree species: Cordia millenii, West African Cordia; Entandrophragma angolense, tiama mahogany; and Lovoa trichilioides, African walnut, within a single montane forest. Additionally, we assessed the diversity of West African Cordia between forests at a local and regional scale. Results indicate that for our focal loci, in all three species, there is a general lack of chloroplast genetic diversity. Our study is particularly relevant because it considers genetic diversity among multiple tree species simultaneously. This work represents the first study of its kind in the region, and will pioneer the way for future conservation genetic studies in montane Nigeria.